2015
DOI: 10.3997/2214-4609.201412723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Matrix Wettability CO2 Assisted Gas-oil Garvity Drainage in Naturally Fractured Reservoirs

Abstract: SUMMARYThe wettability behavior of the matrix block is one of the major factors controlling the effectiveness of the employed EOR methods in NFRs. Water injection in NFRs with mixed-wet or effectively oil-wet matrix blocks usually results in low oil recoveries. In this case, gas injection is considered to be an alternative process, where the process benefits from the gravity forces and the process is called gas-oil gravity drainage. In this study, the effect of matrix wettability on the efficiency of gravity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…In gas assisted gravity drainage (GAGD) oil recovery is influenced by reservoir rock and fluid specific properties, such as heterogeneity of the formation, wettability, oil and gas density, oil and gas viscosity, viscous force, capillary force, gravity, gas injection rate, and gas-oil miscibility or interfacial tension (Catalan et al, 1994;Caubit et al, 2004;Parsaei and Chatzis, 2011;Wu et al, 2013;Ameri et al, 2015;Khorshidian et al, 2017) Parsaei and Chatzis (2011) through a systematic experimental study investigated the impact of reservoir wettability variations at the macroscopic scale on oil recovery efficiency in gravity-assisted inert gas injection (GAIGI) process for tertiary recovery of residual oil by waterflooding. Obtained experimental results showed that for a positive oil-spreading coefficient, the continuity of water-wet portions of the heterogeneous porous medium favors the tertiary oil recovery through the film flow mechanism.…”
Section: Impact On Gas-assisted Drainage Processmentioning
confidence: 99%
See 1 more Smart Citation
“…In gas assisted gravity drainage (GAGD) oil recovery is influenced by reservoir rock and fluid specific properties, such as heterogeneity of the formation, wettability, oil and gas density, oil and gas viscosity, viscous force, capillary force, gravity, gas injection rate, and gas-oil miscibility or interfacial tension (Catalan et al, 1994;Caubit et al, 2004;Parsaei and Chatzis, 2011;Wu et al, 2013;Ameri et al, 2015;Khorshidian et al, 2017) Parsaei and Chatzis (2011) through a systematic experimental study investigated the impact of reservoir wettability variations at the macroscopic scale on oil recovery efficiency in gravity-assisted inert gas injection (GAIGI) process for tertiary recovery of residual oil by waterflooding. Obtained experimental results showed that for a positive oil-spreading coefficient, the continuity of water-wet portions of the heterogeneous porous medium favors the tertiary oil recovery through the film flow mechanism.…”
Section: Impact On Gas-assisted Drainage Processmentioning
confidence: 99%
“…In addition, owing to the high waterflood residual oil content of the heterogeneous media tested, the oil bank formation occurred much earlier and grew faster, resulting in a higher oil recovery factor. Also, Ameri et al (2015) carried out laboratory experiments and numerical simulation to study the effect of matrix wettability on the efficiency of gravity drainage by gas (CO 2 ) injection. They concluded that for a system with an effectively oil-wet matrix, water is the most non-wetting phase while CO 2 is the intermediate-wetting phase.…”
Section: Impact On Gas-assisted Drainage Processmentioning
confidence: 99%